Tourism and humour - Pearce, Philip L.; Pabel, Anja (Aspects of tourism, 2015)
"This book is dedicated to the advancement of knowledge about humour in all kinds of tourism settings. It discusses the many ways in which humour can occur during tourism exchanges including guided tours, tourism marketing and promotion and travel narratives. Other themes include the role of humour in enhancing the tourist experience, the benefits of tourism humour, considerations of when humour may appear inappropriate in tourism settings and the development of tourism humour theory. The work includes much original material collected by the authors. The book will be of interest to undergraduate and postgraduate students, researchers of tourism as well as humour scholars from other disciplines"--Page 4 of cover.